Oh, Olive! - Cho, Lian (New York : Katherine Tegen Books, an imprint of HarperCollins Publishers, 2023)
"Presenting Olive Chen! The most magnificent and brilliant artist in the whole wide world! Her parents are also artists--serious artists--who paint prim, proper, perfect shapes. They know Olive has the talent to follow in their footsteps. But Olive likes to smear, splatter, splash, and even lick. With a brush in each hand, Olive cascades through town with her friends in tow, painting what she wants to, what she feels--until she reaches her parents' pristine art museum ..." --Provided by Publisher.
new kids book 2025 winter.
Keywords: Art -- Juvenile fiction; Artists -- Juvenile fiction; Painting -- Juvenile fiction; Color -- Juvenile fiction; Artists' tools -- Juvenile fiction; Family life -- Fiction; Art museums -- Fiction; JUVENILE FICTION / Art; Art; Artists; Artists' tools; Color; Painting; Artists -- Juvenile fiction; Artists -- Fiction; Family life -- Juvenile fiction; Art museums -- Juvenile fiction; Artists -- Fiction; Art museums -- Fiction; Fiction; Juvenile works; Picture books